Detection and Characterization of Colistin Heteroresistance in an Enterobacter cloacae ST48 Strain Isolated From Raw Milk in Algeria - Sedrati Tahar; Touati Abdelaziz; Tennah Safia; Menoueri M. Nabil; Seydina M. Diene (Veterinary Medicine and Science)
ABSTRACT An Enterobacter cloacae ST48 isolate exhibiting a colistin‐heteroresistant phenotype was obtained from raw cow milk in Algeria. Two subpopulations were detected, both carrying the blaTEM‐1 gene. While one subpopulation (E. cloacae TS34‐a) was highly susceptible to colistin (MIC 0.06 µg/mL), the other (E. cloacae TS34‐b) was resistant (MIC 8 µg/mL). Population analysis profiling (PAP) confirmed heteroresistance. PCR amplification revealed the absence of mcr genes in both subpopulations. However, multiple non‐synonymous mutations, including a stop‐codon mutation in phoP gene, were found in the resistant subpopulation. This is the first report of colistin‐heteroresistant E. cloacae isolated from raw milk, underscoring the importance of vigilance in the dairy industry and food safety.